1997
DOI: 10.1108/08876049710176024
|View full text |Cite
|
Sign up to set email alerts
|

Radio advertising information strategy: differences between services and products

Abstract: Discusses how basic differences between services and products may affect advertising strategy and tactics. Examines a large number of broadcast radio adverts to study the information strategy used in service and product advertisements. Posits that the information commonly used in adverts for services and products was found to differ sharply. Presents one rationale for these information differences using concepts from the services literature. Offers suggestions for improving broadcast advertising effectiveness … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 13 publications
0
16
0
Order By: Relevance
“…Grove, LaBand, and Pickett (1995) found that services advertisers appeared to use more rational appeals than do product advertisers. Abernethy and Gray (1997) demonstrated that service marketers included more information in radio commercials so as to concretize service offerings in consumers' minds and lower risk perceptions. In contrast, Cutler and Javalgi (1993) reported that emotional appeals are seen more often in service advertising.…”
Section: Appeal Strategies and Service Typesmentioning
confidence: 99%
“…Grove, LaBand, and Pickett (1995) found that services advertisers appeared to use more rational appeals than do product advertisers. Abernethy and Gray (1997) demonstrated that service marketers included more information in radio commercials so as to concretize service offerings in consumers' minds and lower risk perceptions. In contrast, Cutler and Javalgi (1993) reported that emotional appeals are seen more often in service advertising.…”
Section: Appeal Strategies and Service Typesmentioning
confidence: 99%
“…Overall, our decision about the choice of radio and newspaper ads, to some degree, is supported by several marketing scholars including Abernethy and Butler (1992) and Abernethy et al (1997). In their research, Abernethy et al (1997) found that compared with magazine and television, radio tends to have more advertisements and with many information cues.…”
Section: Journal Of African Businessmentioning
confidence: 67%
“…In their research, Abernethy et al (1997) found that compared with magazine and television, radio tends to have more advertisements and with many information cues. The authors concluded that, radio advertising contains far more information than magazine or television advertising and that radio advertisements attract more new customers.…”
Section: Journal Of African Businessmentioning
confidence: 99%
“…For example, services advertisements frequently omit such information as price and availability (Abernethy and Butler, 1992) and make more frequent use of emotional appeals (Cutler and Javalgi 1993). On average, services advertisements provide comparatively more information cues of certain types yet comparatively fewer cues of other types (Abernethy and Butler, 1993;Abernethy, Gray, and Butler, 1997).…”
Section: Distinguishing Characteristics Of Services Advertisementsmentioning
confidence: 99%